Integrated production and quality of Galega olive oil - Peres, M.F. (2010)
IOBC / WPRS Working group “Integrated Protection of Olive Crops” OILB / SROP Groupe de travail “Protection Intégrée des Olivaies ” Proceedings of the meeting Comptes rendus de la réunion at / à Bragança (Portugal) 10-12 October 2007